The Health of Soybean Seeds Produced by Farmer Group in Wonogiri - Hapsari, Ramadhani Yovita Hapsari (Jurnal Fitopatologi Indonesia, 2022)
The Health of Soybean Seeds Produced by Farmer Group in Wonogiri Seed-borne fungal infection is one of the constraints limiting soybean production. Study was conducted to evaluate the health of soybean seeds produced by farmers and become the main seed source for most farmers in Wonogiri Regency. The experiment was carried out following a completely randomized factorial design with two factors, i.e. the origin of the seeds (Genuk, Suru, and Sumberejo Villages) and seed treatment (with and without disinfectant). Seed health testing was conducted using modification of blotter test. Identification of seed-borne fungi was carried out based on morphological characters. The results showed that the seeds from Sumberejo Village had normal germination rates that met the requirements as a seed source. However, soybean seeds produced by the farmers in Wonogiri do not meet the requirements as healthy seeds. Seeds from Suru and Genuk Villages were infected and contaminated by Aspergillus niger and A. flavus with an average infection of 90%. These two fungi dominate the infection and contamination of soybean seeds. The use of disinfectants is able to suppress infection and contamination of Aspergillus spp.